The impact of perceived social support on athletic engagement among elite track and field athletes: an integrated perspective based on self-determination theory and social resources theory - Li, Xue; Li, Hengyu; Hwang, Jin; Gao, Weijie (Frontiers in Psychology, 2026)
BackgroundFrom the perspectives of Self-Determination Theory (SDT) and Social Resource Theory (SRT), social support is regarded as a crucial contextual factor influencing athletes’ psychological functioning and engagement. However, the mechanisms through which perceived social support affects athletic engagement, particularly the mediating role of role identity, remain insufficiently explored.PurposeThis study aimed to examine the relationship between perceived social support and athletic engagement among elite track and field (TF) athletes, and to investigate the mediating role of role identity from an integrated SDT and SRT framework.ResultsThe results indicated that: (1) perceived social support and its dimensions were significantly and positively associated with athletic engagement among elite TF athletes; (2) role identity was positively related to athletic engagement and partially mediated the relationship between perceived social support and athletic engagement; and (3) among the four dimensions of social support, esteem support and tangible support demonstrated the strongest and largely comparable total effects on athletic engagement, whereas emotional support and informational support showed relatively weaker associations.ConclusionThese findings suggest that perceived social support plays both direct and indirect roles in enhancing athletic engagement among elite track and field athletes, with role identity serving as a key mediating mechanism. Strengthening esteem and tangible support, as well as fostering athletes’ role identity, may be effective strategies for promoting sustained athletic engagement.